A Cross-Sectional Survey to Assess Biorisk Management System in Research and Diagnostic Laboratories in Khyber Pakhtunkhwa, Pakistan - Muhammad, Javed; Sarwar, Samreen; Khan, Tariq; Qasmi, Shamsul Arfin; Ikram, Aamer; Ahmad, Ghufran; Zahid, Maria; Durrani, Rida Haroon; Ahmed, Furqan (Frontiers in Public Health, 2021)
Financial, cultural, and managerial hurdles have made biosafety and biosecurity measures difficult in resource-constrained countries like Pakistan. Because of increasing awareness of biorisk management, diagnostic and research laboratories have made major advances in biosafety and biosecurity in the recent decade. As a result, identifying and addressing gaps in biorisk management has never been more critical. The purpose of this study was to assess the current situation of personal protective equipment (PPE), biosafety behavior, waste management, biosafety and biosecurity measures, training and safety, and health services in diagnostic and research laboratories across Pakistan's Khyber Pakhtunkhwa (KP) province. We adapted the WHO Laboratory Assessment tool (2012) and CWA 15793 (Biorisk management guidelines) for conducting a cross-sectional survey, which was distributed among various laboratories in KP. The survey included 30 laboratories, including 11 diagnostic and 19 research laboratories. In comparison to diagnostic laboratories, biorisk management practices in research laboratories were better in terms of PPE, biosafety behavior, waste management, biosafety measures, biosecurity measures, trainings, and safety and health services. KP laboratories' biorisk management practices have improved over time, according to our findings. However, we were able to identify inadequacies that would require considerable improvements to the current setups based on the WHO and CWA 15793 recommendations. Organizations can tailor their biosafety measures and training to address identified gaps using the presented KP snapshot.